A comprehensive review of mathematical models of photo fermentation. (19th May 2021) - Policastro, Grazia; Luongo, Vincenzo; Frunzo, Luigi; Fabbricino, Massimiliano
Abstract: This work aims at analyzing and comparing the different modeling approaches used to date to simulate, design and control photo fermentation processes for hydrogen production and/or wastewater treatment. The study is directed to researchers who approach the problem of photo fermentation mathematical modeling. It is a useful tool to address future research in this specific field in order to overcome the difficulty of modeling a complex, not totally elucidate process. We report a preliminary identification of the environmental and biological parameters, included in the models, which affect photo fermentation. Based on model features, we distinguish three different approaches, i.e. kinetic, parametric and non-ideal reactors. We explore the characteristics of each approach, reporting and comparing the obtained results and underlining the differences between models, together with the advantages and the limitations of each of them. The analysis of the approaches indicates that Kinetic models are useful to describe the process from a biochemical point of view, without considering bio-reactor hydrodynamics and the spatial variations that Parametric Models can be utilized to study the influence and the interactions between the operational conditions. They do not take into account the biochemical process mechanism and the influence of reactor hydrodynamics. Quite the opposite, non-ideal reactors models focus on the reactor configuration. Otherwise, the biochemical description of purple non-sulfur bacteria activities is usually simplified. This review indicates that there still is a lack of models that fully describe photo fermentation processes.